Integrating Theory of Planned Behavior with Local Wisdom: A Study of Muslim Tourists’ Revisit Intention in Indonesia - Permadi, Lalu Adi; Wardana, I Made; Ekawati, Ni Wayan; Piartrini, Putu Saroyeni; Setiawan, Putu Yudi (Journal of Cultural Analysis and Social Change, 2026)
Halal tourism has become a strategic priority in Indonesia, with Lombok promoted as a leading Muslim-friendly destination. Yet despite strong policy support, revisit intention among domestic Muslim tourists remains constrained by uneven halal services, limited trust, and cultural underutilization. This study investigates the determinants of revisit intention by integrating the Theory of Planned Behavior (TPB) with destination development factors and introducing a local wisdom–based destination image, while testing halal destination attributes as a moderator. Using a mixed-methods design, Sasak cultural values were first explored to develop locally grounded indicators, followed by a survey of 450 Muslim tourists analyzed with PLS-SEM. Results show that attitude, destination trust, and local wisdom–based image significantly enhance revisit intention, while perceived non-halal risk has no meaningful effect. Halal destination attributes were not found to moderate these relationships, highlighting the need for strategies beyond basic halal provisions. The findings advance TPB by embedding cultural and contextual dimensions, while practically positioning Lombok as a model of halal tourism grounded in cultural depth and sustainability.